Biomechanical assessment of motor abilities in male handball players during the annual training macrocycle - Sacewicz, T.; Bodasinski, S.; Sliwa, M.; Szyszka, P.; Mazur, Z.; Czaplicki, A. (Polish Journal of Sport and Tourism, 2016)
Introduction. The aim of the study was to determine the torque of the knee extensors and flexors of the lead lower limb, the torque of the shoulder extensors and flexors of the dominant upper limb, and the torque generated by the muscles of the kinematic chain going from the trail lower limb to the hand of the dominant limb in male handball players during the annual training macrocycle. Changes in jump height and throwing velocity were also investigated. Material and methods. The study involved 13 handball players from a Polish second-league team. The measurements were performed four times: at the beginning of the preparation period, at the beginning of the season, at the end of the first part of the season, and at the end of the second part of the season. Torque was measured in isokinetic and isometric conditions. Jumping ability was tested using a piezoelectric platform, and throwing velocity was measured with a speed radar gun. Results. The study found statistically significant differences between the relative torque values of the knee extensors (p < 0.002) and flexors (p < 0.003) of the lead leg measured in isokinetic conditions between the first three measurements and the final one. Isokinetic measurement of the torque of the muscles of the kinematic chain going from the trail leg to the hand of the dominant arm decreased in a statistically significant way at the end of the season. As for the results of the measurement of the torque of the shoulder extensors and flexors in static conditions, no statistically significant differences were observed between the four measurements. However, statistically significant differences were noted in jumping ability and throwing velocity in the annual training macrocycle. Conclusions. The results of the study indicate that there is a need to perform regular assessments of players` strength and jumping ability during the competition period. There is a need to modify the training methods used during the preparation period and in the second part of the season as well as to individualise training at the end of the competition period.